Literature Study on Transformational Leadership Style and Quality of Education Based on Child-Friendly Schools (CFS) - Randy Yuki Pratama; Sowiyah; Siti Rahma Sari (Al-Qalam Institue, 2026)
This study aims to examine how transformational leadership of school principals contributes to improving educational quality within the framework of Child-Friendly Schools (CFS). A literature review method was employed by systematically analyzing relevant national and international scholarly sources that discuss transformational leadership and child-friendly education. The findings indicate that the application of the four core dimensions of transformational leadership—idealized influence, inspirational motivation, individualized consideration, and intellectual stimulation—supports the development of high-quality school policies aligned with the fundamental principles of child-friendly schools. These leadership practices encourage the creation of safe, inclusive, and supportive learning environments that respect and fulfill students’ rights. Furthermore, the implementation of child-friendly educational practices contributes to students’ character development and enhances the overall quality of schools. The study implies that transformational leadership is a strategic approach for school principals in fostering sustainable educational improvement through child-friendly school policies and practices. Strengthening leadership capacity in this area is therefore essential to ensure the successful implementation of child-friendly education.